Predicting the spatial organization of chromosomes using epigenetic data. Issue 1 (December 2015) - Mourad, Raphaël; Cuvier, Olivier
Abstract Chromosome folding can reinforce the demarcation between euchromatin and heterochromatin. Two new studies show how epigenetic data, including DNA methylation, can accurately predict chromosome folding in three dimensions. Such computational approaches reinforce the idea of a linkage between epigenetically marked chromatin domains and their segregation into distinct compartments at the megabase scale or topological domains at a higher resolution. Please see related articles:http://dx.doi.org/10.1186/s13059-015-0741-y andhttp://dx.doi.org/10.1186/s13059-015-0740-z